2013
DOI: 10.1371/journal.pone.0054559
|View full text |Cite
|
Sign up to set email alerts
|

QTL for Yield Traits and Their Association with Functional Genes in Response to Phosphorus Deficiency in Brassica napus

Abstract: BackgroundOilseed rape (Brassica napus L.) is one of the most important oil crops. A primary limitation to the cultivation of this crop is the lack of available phosphorus (P) in soils. To elucidate the genetic control of P deficiency tolerance in Brassica napus, quantitative trait locus (QTL) for seed yield and yield related-traits in response to P deficiency were identified using a double haploid mapping population (TN DH) derived from a cross between a P-efficient cultivar, Ningyou 7 and a P-inefficient cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 50 publications
4
40
0
2
Order By: Relevance
“…1). Similar results were reported by Zhao et al (2012) and Shi et al (2013) who reported respectively that Brassica napus grown under boron and phosphorus deficiency showed highly variation in PH, SP, PP and especially SY.…”
Section: Qtls For Mungbean Yield and Yield-related Traits Grown Undersupporting
confidence: 90%
See 1 more Smart Citation
“…1). Similar results were reported by Zhao et al (2012) and Shi et al (2013) who reported respectively that Brassica napus grown under boron and phosphorus deficiency showed highly variation in PH, SP, PP and especially SY.…”
Section: Qtls For Mungbean Yield and Yield-related Traits Grown Undersupporting
confidence: 90%
“…The nutrient use efficiency of a genotype is defined as the ability to produce higher yield in soils with limited nutrient supplies. A better understanding of genetic control of the macro-or micronutrient deficiency can be achieved by QTL mapping of yield and yield-related traits as demonstrated by Zhao et al (2012) and Shi et al (2013). In mungbean, the information of QTLs for yield and yield-related traits under iron deficiency is not known, although these traits can be employed as indicators for measuring resistance to iron deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…More recent efforts have also generated integrated maps for B. napus (Schwarzacher et al 2008;Würschum et al 2012;Delourme et al 2013). Using map integration, QTL hotspots for many agronomic traits have previously been identified in B. napus, including plant height (Mei et al 2009), flowering time (Long et al 2007), seed yield ), phosphorus efficiency Shi et al 2013), glucosinolate concentration (Feng et al 2012;Uzunova et al 1995), seed oil content (Delourme et al 2006;Qiu et al 2006), heterosis-related traits (Basunanda et al 2010;Shi et al 2011) and disease resistance (Pilet et al 2001;Manzanares-Dauleux et al 2000;Werner et al 2008;Kaur et al 2009). …”
Section: B Rapa Genome Was Sequenced (The Brassica Rapa Genome Sequementioning
confidence: 99%
“…B. napus (canola or rapeseed) is planted worldwide, and is an essential source of oil, fodder and biodiesel. Since the first molecular linkage map in B. napus was reported (Landry et al 1991), thousands of important QTLs for traits such as seed yield, yield components, biomass, flowering time, seed quality, disease resistance or tolerance, mineral nutrition and other yield-related traits have been identified in B. napus (Basunanda et al 2010;Cai et al 2012;Chen et al 2007;Fan et al 2010;Feng et al 2012;Long et al 2007;Rygulla et al 2008;Yang et al 2011;Shi et al 2013;Raman et al 2013). However, to date, it is still very difficult for Brassica breeders to effectively utilize this large body of QTL data.…”
Section: Introductionmentioning
confidence: 99%
“…There are more known QTLs, often at very early growth stages (Su et al , 2009Yang et al 2010, related to yield components under low P conditions (Su et al 2009;Chin et al 2010;Ding et al 2012;Gamuyao et al 2012;Shi et al 2013), to seed P concentrations Zhao et al 2008), to P uptake capability and morphological adaptation e.g. tiller number Wissuwa et al 1998Wissuwa et al , 2002Chin et al 2010;Gamuyao et al 2012) or root morphology (Zhu et al 2005a(Zhu et al , b, 2006Liang et al 2010;.…”
Section: Quantitative Trait Loci Identificationmentioning
confidence: 99%